Effect of Lymphadenectomy on Survival in Early-Stage Type II Endometrial Carcinoma and Carcinosarcoma. (10th April 2020) - Vatansever, Dogan; Sozen, Hamdullah; Sahin Ersoy, Gulcin; Giray, Burak; Topuz, Samet; Iyibozkurt, A. Cem; Salihoglu, Yavuz
Abstract : Purpose . We aimed to investigate whether systematic pelvic and paraaortic lymph node dissection delivers any survival advantage in a subgroup of patients with type II endometrial carcinoma and carcinosarcoma. Methods . We evaluated 135 patients with clinically early-stage (Stage I-II) type II endometrial carcinoma and carcinosarcoma who underwent systematic pelvic and paraaortic lymph node dissection or who did not undergo any lymph node dissection. Results . Overall survival (OS) and recurrence-free survivals (RFS) were significantly longer in the systematic lymph node dissection group (hazard ratio 0.28, 95% CI 0.13–0.62 p = 0.002 for OS and hazard ratio 0.31, 95% CI 0.14–0.69 p = 0.004 for RFS). Multivariate analysis showed that lymph node dissection, age, lymph node metastasis, and adjuvant therapy were independent prognostic variables of OS and RFS. Conclusions . Systematic pelvic and paraaortic lymph node dissection independently and significantly prolongs the survival of patients with early-stage type II endometrial carcinoma and carcinosarcoma.